The Feasibility of Professional Schools: An Empirical Study. - Bremser, Wayne G.; Brenner, Vincent C.; Dascher, Paul E. (The Accounting Review, 1977)
ABSTRACT: This paper reports on an attitudinal survey of accounting department chairpersons and college of business deans from AACSB schools. The questionnaire focused on the most crucial issues that have emerged from the debate about schools of professional accountancy. These issues were classified into four categories–autonomy, identity, relationships with practitioners and deterring factors. The deans viewed the deterring factors as being the most important issues; the chairpersons ranked autonomy as the most significant. Considerable disagreement over the specific issues was discovered. Overall, few deans seem to favor the professional school concept.